Utility of HbA1c assessment in people with diabetes awaiting liver transplantation. Issue 11 (30th April 2019) - Bhattacharjee, D.; Vracar, S.; Round, R. A.; Nightingale, P. G.; Williams, J. A.; Gkoutos, G. V.; Stratton, I. M.; Parker, R.; Luzio, S. D.; Webber, J.; Manley, S. E.; Roberts, G. A.; et al.
Abstract: Aims: To investigate the relationship between HbA1c and glucose in people with co‐existing liver disease and diabetes awaiting transplant, and in those with diabetes but no liver disease. Methods: HbA1c and random plasma glucose data were collected for 125 people with diabetes without liver disease and for 29 people awaiting liver transplant with diabetes and cirrhosis. Cirrhosis was caused by non‐alcoholic fatty liver disease, hepatitis C, alcoholic liver disease, hereditary haemochromatosis, polycystic liver/kidneys, cryptogenic/non‐cirrhotic portal hypertension and α‐1‐antitrypsin‐related disease. Results: The median (interquartile range) age of the diabetes with cirrhosis group was 55 (49–63) years compared to 60 (50–71) years ( P =0.13) in the group without cirrhosis. In the diabetes with cirrhosis group there were 21 men (72%) compared with 86 men (69%) in the group with diabetes and no cirrhosis ( P =0.82). Of the group with diabetes and cirrhosis, 27 people (93%) were of white European ethnicity, two (7%) were South Asian and none was of Afro‐Caribbean/other ethnicity compared with 94 (75%), 16 (13%), 10 (8%)/5 (4%), respectively, in the group with diabetes and no cirrhosis ( P =0.20). Median (interquartile range) HbA1c was 41 (32–56) mmol/mol [5.9 (5.1–7.3)%] vs 61 (52–70) mmol/mol [7.7 (6.9–8.6)%] ( P <0.001), respectively, in the diabetes with cirrhosis group vs the diabetes without cirrhosis group. The glucose concentrations were 8.4 (7.0–11.2) mmol/l vs 7.3 (5.2–11.5) mmol/l ( P =0.17). HbA1c was depressed by 20 mmol/mol (1.8%; P <0.001) in 28 participants with cirrhosis but elevated by 28 mmol/mol (2.6%) in the participant with α‐1‐antitrypsin disorder. Those with cirrhosis and depressed HbA1c had fewer larger erythrocytes, and higher red cell distribution width and reticulocyte count. This was reflected in the positive association of glucose with mean cell volume ( r =0.39) and haemoglobin level ( r =0.49) and the negative association for HbA1c ( r =–0.28 and r =–0.26, respectively) in the diabetes group with cirrhosis. Conclusion: HbA1c is not an appropriate test for blood glucose in people with cirrhosis and diabetes awaiting transplant as it reflects altered erythrocyte presentation. What's new?: HbA1c may not be an accurate reflection of blood glucose for the diagnosis/monitoring of diabetes in people with other illnesses or on certain drugs; people with diabetes and liver disease awaiting transplantation are one such group. HbA1c was found to be depressed relative to random plasma glucose by 20 mmol/mol in people with diabetes and cirrhosis ( n = 28) compared to people with diabetes but no liver disease ( n = 125); however, HbA1c was elevated in one person with cirrhosis attributable to α‐1‐antitrypsin disorder. Compromised HbA1c may be related to haematological differences associated with liver disease involving erythrocyte half‐life, with shorter/longer times giving less/more opportunity for glycation of haemoglobin.